In silico studies and biological evaluation of chalcone-based 1,5-benzothiazepines as new potential H1N1 neuraminidase inhibitors - Neni Frimayanti, Marzieh Yaeghoobi, Hamid Namavar, Ihsan Ikhtiarudin, Meysam Afzali (Journal of Applied Pharmaceutical Science, 2020)
1,5-Benzothiazepines are benzo-fused seven-membered heterocycles. Due to their biological activities against a wide spectrum of targets, they are of particular interest for drug discovery. However, their antiviral activities and in silico studies of the binding to their biological targets have not been extensively investigated. In this study, we tested antiviral activities of twelve 1,5 benzothiazepine compounds (1,5-benzothiazepines) against the H1N1 influenza virus also known as swine flu. The target of chalcone-based 1,5-benzothiazepines was viral protein, H1N1 neuraminidase, and the binding was monitored using 4-methylumbelliferyl)-a-D-N-acetylneuraminic acid assay [2′-(4-methylumbelliferyl)- α-D-N-acetylneuraminic acid]. 2,3-didehydro-2-deoxy-N-acetylneuraminic acid (DANA) has been used as a positive control. Before the bioassay, computational pipelines were drawn to identify the potential bioactive compounds. Results from the docking revealed that compound MA10 bound favorably to the active site on H1N1 neuraminidase and the free energy of binding was −8.8 kcal/mol. We have also shown the importance of hydrophobic interactions, hydrogen bonds, and aromatic ring features for enhancing the biological activity of the pharmocophore. MA10 was also stable in the molecular dynamics simulation with the lowest binding energy conformation (i.e., energy minimum to bound conformation with the protein). Moreover, based on the Lipinski’s rule of five, MA10 showed druglikeness properties. Although neither of the tested benzothiazepines reached the inhibitory activity measured for DANA, their in silico behavior accorded well with that in in vitro assays. Among all the compounds tested with H1N1 neuraminidase, MA10 exhibited the best inhibitory activity, so this benzolog could be used against H1N1. We, therefore, suggest an in vitro plus in silico strategy to be employed in the early-stage drug-discovery process, which might help us to identify drug candidates successfully with minimum research time and costs.
Keywords: H1N1, neuraminidase, docking, Molecular dynamic, ADME.